UJI MODEL HIDROLIK FISIK (UMH-FISIK) PELIMPAH BENDUNGAN CIBEET DI KABUPATEN BOGOR - Riezky Tazkia Pratiwi; Yeri Sutopo (DAS Institute, 2022)
Among the vital components of a dam is the spillway structure. Therefore, the building requires testing of physical hydraulic models, one of which is carried out at the Water Hydraulics and Geotechnical Center laboratory. This physical hydraulic model test study aims to analyze the hydraulic behavior of the dam spillway, mainly the discharge curve and flow elevation, average flow velocity, flow direction pattern, and hydrostatic pressure. This study uses a physical hydraulic model (modeling), which is a research method that focuses on 3-dimensional physical modeling and using the initial design from the consultant (series 0) by modeling some of the core parts of the dam such as spillway structures, dam body structures, launch channels, energy dampers, some of the contours of the river upstream, and some of the contours of the river downstream. The research instrument used were: Thompson discharge measuring instrument, level meter as a means of predicting water level elevation, current meter velocity measuring instrument, floating object as a research aid, a piezometer to determine hydrostatic pressure. The results showed that the spillway capacity could drain the PMF return period discharge (QPMF = 2091,75 m3/s) with the available guard height of 1,25 m, meeting the planning criteria of 0,75 m. At the Q2th and Q25th discharges, there is no hydraulic jump in the energy reducer and leads directly to the transition channel. In contrast, at the Q100th and Q1000th discharges, a hydraulic jump occurs in the energy reducer. The flow velocity, downstream of the spillway, especially on the left side of the guide wall, was recorded at a relatively high velocity, allowing turbulence to occur. The flow direction pattern that occurs upstream of the reservoir is reasonably even towards the spillway, and there is no crossflow. There is negative pressure at the piezometer point P5 with a 2-year return discharge of -0,25 N/m2, a 25-year return discharge of -0,25 N/m2, and a 100-year return discharge of -0,15 N/m2, which is still within the safe limits and does not exceed the allowable provisions, namely -1.00 m (for pairs) and -4.00 m (for concrete).